Pengaruh Digital Marketing dan Service Quality terhadap Repurchase Intention melalui Customer Experience pada Coffee Nako di Kota Semarang - Ulinnuhha Arga Febrika; Wahyu Setiawan (Lembaga Yasin AlSys, 2026)
The rapid development of the coffee shop industry in Indonesia has intensified competition and encouraged business operators to retain customers through repeat purchases. However, some Nako Coffee customers have not demonstrated an intention to repurchase products despite being familiar with and having visited the outlet. This study aims to analyze the effects of digital marketing and service quality on repurchase intention, with customer experience as a mediating variable among Nako Coffee customers in Semarang City. The study employed a quantitative approach using a verification method. Primary data were collected through questionnaires administered to 100 respondents who had made purchases at least twice at Nako Coffee in Semarang City and were selected using purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that digital marketing and service quality had positive and significant effects on customer experience and repurchase intention. Customer experience also had a positive and significant effect on repurchase intention and was able to mediate the effects of digital marketing and service quality on repurchase intention. This study concludes that strengthening digital marketing strategies and improving service quality can create positive customer experiences and encourage repurchase intention. These findings reinforce the mediating role of customer experience in the relationships among digital marketing, service quality, and repurchase intention and provide practical implications for Nako Coffee management in developing integrated customer retention strategies.